Relationship between eating habits, probiotic and prebiotic consumption in the profile of the intestinal microbiota: Integrative review (Research, Society and Development, 2020)
Intestinal microbiota is the term that refers to the population of microorganisms that make up the gastrointestinal tract. The composition of this ecosystem plays a fundamental role in maintaining the health of the host. Genetic and environmental factors involve the multiple causes of NCDs with emphasis on diets with high energy density and physical inactivity and the role of bacteria that colonize the intestine as etiopathogenic agents is highlighted because they have a high potential for intervention, which justifies an in-depth study on the role of intestinal microbiota whose composition is capable of determining predisposition or protection against diseases. The study is an integrative review of the literature in Nutrition, with the aim of understanding the relationship between eating habits and the modulation of the intestinal microbiota and inflammatory processes in the body and the influence of probiotic supplementation in this process. 9 scientific articles with the highest number of production in the years 2018 and 2019 were researched and examined. The analyzed articles pointed out that the human microbiota has an impact on health, nutrition and well-being and should be the object of continuous study since scientific evidence grows showing the factors involved in the variation in the composition of the microbiota between individuals in terms of health and disease.